2022
DOI: 10.1371/journal.pone.0277865
|View full text |Cite
|
Sign up to set email alerts
|

Temperature moderates impact of formulated moxidectin on seed germination of three temperate grassland species

Abstract: Formulations of macrocyclic lactone anthelmintics such as moxidectin are regularly administered to sheep to combat parasites. A disadvantage of these pharmaceuticals are their side effects on non-target organisms when entering the environment. Little is known about anthelmintic effects on plant reproduction and whether the effects depend on environmental factors. For ecological and methodological reasons, we aimed at testing whether temperature affects the efficacy of a common moxidectin-based formulation on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In formulated MOX (Cydectin), we found the effects on seed germination, especially on germination percentage (GP) and mean germination time (MGT), increase in strength with increasing concentrations for most species, which is in accordance with previous studies (Eichberg et al . 2016, 2022). Across all species, this pattern was similarly observed for formulated IVM (Oramec), but not for the four pure substances, where we found no regularly increasing or decreasing concentration‐specific response patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In formulated MOX (Cydectin), we found the effects on seed germination, especially on germination percentage (GP) and mean germination time (MGT), increase in strength with increasing concentrations for most species, which is in accordance with previous studies (Eichberg et al . 2016, 2022). Across all species, this pattern was similarly observed for formulated IVM (Oramec), but not for the four pure substances, where we found no regularly increasing or decreasing concentration‐specific response patterns.…”
Section: Discussionmentioning
confidence: 99%
“…At species level, in all six tested ML pharmaceuticals, non‐linear and species‐specific response patterns were found, which is also in accordance with previous studies (Eichberg et al . 2016, 2022). We found that the highest concentration of MLs (10.0 mg·l −1 ) affected seeds of most test species, whereas at lower concentrations (0.1, 1.0 mg·l −1 ) effects were less frequent and less consistent (except for pure abamectin).…”
Section: Discussionmentioning
confidence: 99%